2013
DOI: 10.1016/j.jns.2013.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Neuroradiologic correlates of clinical disability and progression in the X-Linked leukodystrophy Pelizaeus–Merzbacher disease

Abstract: Objective To determine whether quantitative measure of magnetic resonance imaging data from patients with the inherited leukodystrophy, Pelizaeus–Merzbacher disease (PMD) correlates with clinical severity or progression. Methods In our current work we have analyzed the clinical phenotypes and MRI scans of 51 male patients with PMD and 10 female carriers for whom the PLP1 genotype had been determined. In addition, we developed a 32-point functional disability scoring (FDS) system for PMD, and validated it for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 34 publications
(23 reference statements)
4
35
2
6
Order By: Relevance
“…For adult patients presenting severe cerebral atrophy on conventional MRI, the decreased size of tractograms may reflect WM atrophy or loss of connectivity. Laukka et al [11], argued prominent WM atrophy in PMD/SPG2 patients, whereas we observed parallel WM/GM atrophy over time on conventional MRI [9]. Taken together, the combination of patients' clinical evolution, progressive global atrophy, GM microstructure changes on DTI, and progressive WM fiber disappearance on tractography converge to confirm that PLP1-related disorders are global central nervous system diseases affecting both WM and GM.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For adult patients presenting severe cerebral atrophy on conventional MRI, the decreased size of tractograms may reflect WM atrophy or loss of connectivity. Laukka et al [11], argued prominent WM atrophy in PMD/SPG2 patients, whereas we observed parallel WM/GM atrophy over time on conventional MRI [9]. Taken together, the combination of patients' clinical evolution, progressive global atrophy, GM microstructure changes on DTI, and progressive WM fiber disappearance on tractography converge to confirm that PLP1-related disorders are global central nervous system diseases affecting both WM and GM.…”
Section: Discussionsupporting
confidence: 75%
“…The second decade is marked by neurological deterioration with cortico-subcortical atrophy on MRI, leading to severe quadriplegia, amyotrophy, optic atrophy, and cognitive decline in young adults, even in the mildest forms [10]. Several recent studies have underlined the correlation between clinical severity and brain atrophy on MRI [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…We obtained primary fibroblasts de-identified except for their mutation and clinical severity impression (mild, moderate, or severe) or functional disability score (ranging from 1 [most severe] to 32 [least severe]). 54 Our panel ultimately consisted of 12 lines with various PLP1 mutations (Figures 1A and 1B and Table S2) and seven normal control lines (Table S3). For two individuals, PMD2 and PMD10, axial T2-weighted MRI taken when they were ages 4 and 12 years, respectively, was also available (Figures 1C and 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Such MRI is highly representative of children with moderate to severe PMD and demonstrates both the ambiguity and convergence of clinical presentations across people with disparate PLP1 mutations. [54][55][56] To generate a renewable source of PMD-derived cells, we reprogrammed fibroblasts from all 12 individuals to hiPSCs (see Material and Methods). Two independently derived hiPSC lines per individual were ultimately selected for rigorous characterization.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, conventional MR imaging in ADLD cases showed a significant thinning of CC. Macro-and microstructural changes in CC are typically related to different degrees of cognitive impairment as in Alzheimer's Disease (Di Paola et al, 2010), Fronto-Temporal Dementia (Tartaglia et al, 2012) and in white matter disorders such as Hereditary Diffuse Leukoencephalopathy with Neuroaxonal Spheroids (Kinoshita et al, 2014), Pelizaeus-Merzbacher disease (Laukka et al, 2013) and Metachromatic leukodystrophy (Groeschel et al, 2011). The genu of the CC regulates inter-hemispheric connections between pre-frontal associative areas that are involved in working memory, executive and attentive functions (Aung et al, 2013).…”
Section: Casesmentioning
confidence: 99%